Hubungan Kebugaran Jasmani dengan Tingkat Konsentrasi Peserta Didik dalam Mengikuti Pembelajaran di Sekolah - Andika; Burhan Hambali; Yudi Hendrayana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the relationship between physical fitness and students’ concentration levels during classroom instruction at SMP Indonesia Raya in Bandung. This study employs a quantitative approach with a correlational design to explore the relationship between physical fitness and students’ concentration levels at SMP Indonesia Raya. The study population consisted of all students at SMP Indonesia Raya Bandung from grades 7 through 9, totaling 75 students. The primary instrument used to measure students’ physical fitness in this study was the Nusantara Student Fitness Test (TKPN). The results of the study indicate that the students’ physical fitness levels, as measured by the Nusantara Student Fitness Test, generally fell into the moderate category, with an average score of 2.1600. Physical condition among students tends to vary because the standard deviation is fairly high. A similar pattern was also observed in students’ ability to concentrate on learning, as assessed using the Grid Concentration Test, where their overall visual focus performance fell within the moderate range, with a more even or homogeneous distribution of data. Research findings indicate that when students are in top physical condition, their ability to concentrate while learning in class also improves. Keywords: Grid Concentrtion Test, Physical Fitness Test, Concentration in Learnin, Students, Tes Kebugaran Pelajar Nusantara